Functional Consequences of Interactions between Pax9 and Msx1 Genes in Normal and Abnormal Tooth Development - Takuya Ogawa; Hitesh Kapadia; Jian Q. Feng; Rajendra Raghow; Heiko Peters; Rena N. D’Souza (2006)
Pax9 and Msx1 encode transcription factors that are known to be essential for the switch in odontogenic potential from the epithelium to the mesenchyme. Multiple lines of evidence suggest that these molecules play an important role in the maintenance of mesenchymal Bmp4 expression, which ultimately drives morphogenesis of the dental organ. Here we demonstrate that Pax9 is able to directly regulate Msx1 expression and interact with Msx1 at the protein level to enhance its ability to transactivate Msx1 and Bmp4 expression during tooth development. In addition, we tested how a missense mutation (T62C) in the paired domain of PAX9 that is responsible for human tooth agenesis (1) affects its functions. Our data indicate that although the mutant Pax9 protein (L21P) can bind to the Msx1 protein, it fails to transactivate the Msx1 and Bmp4 promoter, presumably because of its inability to bind cognate paired domain recognition sequences. In addition, synergistic transcriptional activation of the Bmp4 promoter was lost with coexpression of mutant Pax9 and wild-type Msx1. This suggests that Pax9 is critical for the regulation of Bmp4 expression through its paired domain rather than Msx1. Our findings demonstrate the partnership of Pax9 and Msx1 in a signaling pathway that involves Bmp4. Furthermore, the regulation of Bmp4 expression by the interaction of Pax9 with Msx1 at the level of transcription and through formation of a protein complex determines the fate of the transition from bud to cap stage during tooth development.